Evaluation of Green Building by Analytic Hierarchy Process and Statistical Inference (Case Study: Sabzevar City) - Masumeh Karami; Ghasem Zolfaghari; Mehri Delsouz (توسعه پایدار شهری)
The main goal of this descriptive and inferential research is to present a green building evaluation system from the point of view of experts. In addition, a multi-criteria decision-making model using the Analytic Hierarchy Method (AHP) is used to evaluate and prioritize the criteria of green buildings. Also, using Wilcoxon and Friedman statistical inference, the importance of green building evaluation system criteria in Sabzevar city has been investigated. The method of work is as follows: first, the criteria of sustainable architecture were determined and the green building evaluation system was developed, and then the weight coefficient of each criterion was determined using Expert choice 11 software. Then 10 buildings from Sabzevar city were randomly selected and the importance of sustainability criteria in these buildings was determined using SPSS 16 software. The results of the paired comparisons of building sustainability criteria indicate that the water criterion with a weight of 0.2 (20%) is the most important among other criteria, followed by the technical quality criteria (weight 0.178). In relation to the investigation of sustainable architecture in Sabzevar city, the results of the Wilcoxon test show that the average of people's responses for most variables is close to the median value (0.625). Also, the results of the Friedman test show the ranking of the criteria so that the technical quality criterion with an average rating equal to 9.35 has won the first rank and the water criterion has obtained the last rank with an average rating equal to 2.10. Considering that from the point of view of the experts, the water standard is the most important, but from the point of view of the owners of the investigated buildings, water is ranked last, it is concluded that explaining and dealing with the water issue, especially in dry climates (such as Razavi Khorasan province) it is very necessary to pay attention to the problems that exist in this field.